PENGARUH SOLVABILITAS DAN RENTABILITAS TERHADAP HARGA SAHAM PERUSAHAAN PERTAMBANGAN SUB SEKTOR LOGAM DAN MINERAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Oktaviani, Hutapea Selly (EKONOMIA, 2019)
Metal commodities in Indonesia are likely to experience a decrease in performance the last few years. The decline in commodities will ultimately lower stock prices. The prices of shares in influence by several factors, one of each is the financial performance of the company. The purpose of this research was to tes, to know and explain the influence of Debt To Eqquity Ratio and Return On Equity against share price.The object of this research in the mining sector of metals and minerals sub sector listed in Indonesia stock exchange year 2013-2017. Variables are used is Debt To Equity Ratio, Return On Equity, and share price. The tecnique of sampling with the purposive sampling and retrieved samples of as much as 7 companies. Reseacrh data using the method of multiple linear regression with a sifnificant level of 0.05.Based on the result analysis of the data by using the partial test (t-test) variable of Debt To Equity Ratio have negative effect not significant against stock prices with regression coefficients of -265,866 with the significance value of 0,245. Return On Equity have a positive effect is not significant on stock price with regression coefficient 6,608 with the significant value of 0,553. Provided F count of 0,937 < F table with a value of significant 0,404 > 0,05.The studies concluded H1 be rejected because Debt To Equity Ratio have negative effect not significant on stock price. H2 because Return On Equity have a positive effect is not signifanct on stock price. H3 was rejected becase Debt To equity Ratio and Return On Equity has not significant expands on the stock.